Evaluation of Natural Bioactive-Derived Punicalagin Niosomes in Skin-Aging Processes Accelerated by Oxidant and Ultraviolet Radiation [Retraction] - Mohamad EA; Aly AA; Khalaf AA; Ahmed MI; Kamel RM; Abdelnaby SM; Abdelzaher YH; Sedrak MG; Mousa SA (Dove Medical Press, 2023)
Mohamad EA, Aly AA, Khalaf AA, et al. Drug Des Devel Ther. 2021;15:3151–3162. The Editor and Publisher of Drug Design, Development and Therapy wish to retract the published article. Concerns were raised regarding the integrity of the HPLC chromatograms presented in Figure 1, where the values of the peaks did not appear to correspond with the values shown along the x-axis. The authors did respond to our queries and explained that their laboratory does not have access to an HPLC device and the HPLC experiments were performed by a third-party. They further explained that errors had been made during calculations of the retention times, but they were unable to explain how this occurred. In addition, discrepancies remained in the retention times of the corrected HPLC chromatograms the authors provided, and there was a lack of adequate data associated with these experiments. The Editor determined that the explanation for the calculation errors and availability of original data were both insufficient and had concerns over the reliability of the reported findings. The Editor requested for the article to be retracted and the authors were notified of this. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.